If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6n + 7n + 4 = 0 Reorder the terms: 4 + -6n + 7n = 0 Combine like terms: -6n + 7n = 1n 4 + 1n = 0 Solving 4 + 1n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1n = 0 + -4 1n = 0 + -4 Combine like terms: 0 + -4 = -4 1n = -4 Divide each side by '1'. n = -4 Simplifying n = -4
| 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 | | 52=(3x+2) | | 3(x+3)+x=2(x+3)-5 | | 9x^2+27x=7 | | y=3x^2-7x-1 | | 0.2(x-2)-0.4(x+2)=-0.2x-0.4 | | (R-2)3+6=38.85 | | 3t+16.9=(11+-29.5) | | 11-2x=2(4-x) | | 10z=6z-10+3z | | (-3x^2y^4)(8xy^3)=0 | | 9x+48=2x+11 | | 20(-3+2x)=(4x)5 | | 10ac-x=3 | | 8(x+6)+x=2(x+2)+7 | | -8(-2x+5)=-136 | | 2(-10-7x)=50 | | 2(5-1.7b)=15.1-7(1.7) | | 2v-3v+3-4v=0 | | (3x-5)(x-8)=0 | | 11+6y-8y=-3+3y |